Effect of density and surface finishing on sound absorption of oil palm frond - Nanthicha Bubparenu (2019)
© 2018, Khon Kaen University,Research and Technology Transfer Affairs Division. All rights reserved. In this study, worthless discarded oil palm fronds were used to produce environmentally-friendly sound absorbing material to replace harmful man-made inorganic fibers. To quantify the properties of sound absorption, oil palm frond fiberboards in various densities, i.e., 0.17, 0.21, 0.26 and 0.30 g cm-3, were produced by traditional soft board production and tested for their sound absorption coefficients at 250, 500, 1000 and 4000 Hertz using a standing wave apparatus assembled following ASTM C-384. The boards with the best sound absorption capacity were selected to cover their surfaces using the nonperforated and 5% perforated wood veneers, and the effects of surface finishing on their sound absorption capacity were rechecked. Results showed that the lower density fiberboards showed better sound absorption at high frequencies. Among these, 0.17 g cm-3 fiberboards displayed the highest sound absorption capacity. Once these boards were finished with the nonperforated wood veneers, the sound absorption coefficients at high frequencies sharply decreased. However, when perforating the veneer sheets, the coefficients of fiberboards increased and were comparable to the ones without any finishing. Therefore, the optimum density of fiberboard and opening surface can enhance the sound absorption capacity of fibers.